Consumers' Attitudes and Behavioural Intentions on Internet Banking in Nepal (Dristikon: A Multidisciplinary Journal, 2023)
Banks and financial institutions have huge opportunities to capture high market share by satisfying customers' transforming attitudes and behaviour towards Internet banking. This paper examines customers' attitudes toward Internet banking and evaluates behavioural intentions regarding technology accessibility in Nepal. Based on the descriptive research design,  384 respondents were considered a sample for the survey. Information about customers' attitudes was gained by analyzing descriptive statistics. Mean, Standard deviation and cross-tab analysis were utilized to examine results. The result declared that 93% of Internet bank users felt it was more effective than traditional service, while the remaining users believed conventional banking was more efficient.  It also found 51% of respondents used it for funds transfer and home banking via the Internet, and 71.6% of respondents agreed that online banking could access from anywhere. Organizing reports, scheduling payments, and transferring money from one account to another is extremely important. The output also indicates that 68 % of respondents were satisfied with Internet banking.